Hubungan Penambahan Berat Badan Ibu Selama Kehamilan Dengan Berat Badan Bayi Lahir (Studi Di Polindes Desa Wonoayu Kecamatan Pilangkenceng Kabupaten Madiun Tahun 2013) - Sari, Dyah Permata (SEKOLAH TINGGI KESEHATAN MAJAPAHIT MOJOKERTO, 2015)
Weight gain during pregnancy in Indonesia are generally low (<10 kg), whereas weight gain is an important indicator of fetal growth. Maternal weight before pregnancy and weight gain during pregnancy is a major determinant of infant weight at birth. The purpose of this study was to determine the relationship between maternal weight gain during pregnancy with birth weight in the Wonoayu Village Pilangkenceng District Madiun. This research used the analytical method with a